Comparison Of Anxiety Levels In Mdr-tb Patients With Individual And Short-term Regimens At Dr. Soebandi Regional General Hospital, Jember, Indonesia - Muhammad Rifqy Alvy Widodo; Ida Srisurani Wiji Astuti; Inke Kusumastuti; Angga Mardro Raharjo; Supangat Supangat; Justina Evy Tyaswati; Noor Fadzilah Zulkifli (Faculty of Medicine Universitas Airlangga, 2024)
Non-Indexed Publication